Loyalty of m-wallet user from a service-dominant logic perspective - Nalal Muna; Mutia Rahmi Pratiwi; Barkah Alkhaliq (Jurnal Manajemen dan Pemasaran Jasa, 2020)
This study aimed to examine the effect of customer perceived value on the loyalty of mobile wallet (m-wallet) users. Payment using mobile wallet offers several benefits for consumer in terms of functional, social, and economic value. Meanwhile, Service-Dominant Logic was used to explain consumer’s experience in utilizing mobile wallet for payment. Furthermore, a quantitativeapproach with questionnaire was used for data collection, and a total of 325 users participated as the respondents. A purposivesampling technique was used to determine the sample criteria i.e. active m-wallet users with a minimum usage of 1 year. The result showed that all the hypotheses are supported. This indicated that customer perceived value consist of functional, economic, and social value, which have positive and significant impact on satisfaction that leads to customer loyalty. Meanwhile, satisfactionis the most salient predictor of customer loyalty. Therefore, financial technology provider needs to pay more attention to customer perceived value, especially in terms of functional, economic and social aspect.